Design, synthesis, and biological evaluation of novel aminopyrimidinylisoindolines as AXL kinase inhibitors - Choi, Min Jung; Roh, Eun Joo; Hur, Wooyoung; Lee, So Ha; Sim, Taebo; Oh, Chang-Hyun; Lee, Sun-Hwa; Kim, Jong Seung; Yoo, Kyung Ho (Pergamon Press Ltd., 2018)
A novel series of aminopyrimidinylisoindoline derivatives 1a-w having an aminopyrimidine scaffold as a hinge region binding motif were designed and synthesized. Among them, six compounds showed potent inhibitory activities against AXL kinase with IC50 values of submicromolar range. Especially, compound 1u possessing (4-acetylpiperazin-1-yl)phenyl moiety exhibited extremely excellent efficacy (IC50 = < 0.00050 mu M). Their in vitro antiproliferative activities were tested over five cancer cell lines. Most compounds showed good antiproliferative activities against HeLa cell line. The kinase panel profiling of 50 different kinases and the selected inhibitory activities for the representative compound 1u were carried out. The compound 1u exhibited excellent inhibitory activities (IC50 = < 0.00050, 0.025, and 0.050 mu M for AXL, MER, and TYRO3, respectively) against TAM family, together with potent antiproliferative activity against MV4-11 cell line (GI(50) = 0.10 mu M) related to acute myeloid leukemia (AML).
Keywords: RECEPTOR TYROSINE KINASES; TAM FAMILY; CANCER; TARGETS; CELLS